2012
DOI: 10.4021/jocmr723w
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of Blockade Following Axillary and Infraclavicular Approaches of Brachial Plexus Block in Uremic Patients

Abstract: IntroductionThis study was aimed to compare the axillary approach performed through multiple injection method and vertical infraclavicular approach performed through single injection method in terms of the sensory and motor block onset, quality, and extent of blocks of brachial plexus in uremic patients who underwent arteriovenous fistula surgery.MethodsForty patients scheduled for creation of arteriovenous fistula with axillary brachial plexus block (group AX, n = 20) or infraclavicular brachial plexus block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although available data are insufficient, DEX is a good local anesthetic (LA) adjuvant that can hasten the onset and prolong the duration of sensory and motor blockade when used in intrathecal or epidural block and looks safe ( 8 ). Some previous studies showed that α 2 adrenergic receptor agonist prolongs the effects of local anesthetics ( 9 - 11 ), however these results are mixed ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although available data are insufficient, DEX is a good local anesthetic (LA) adjuvant that can hasten the onset and prolong the duration of sensory and motor blockade when used in intrathecal or epidural block and looks safe ( 8 ). Some previous studies showed that α 2 adrenergic receptor agonist prolongs the effects of local anesthetics ( 9 - 11 ), however these results are mixed ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of brachial plexus blockade to provide anaesthesia for upper limb fistula formation in patients with end‐stage renal failure is a safe and well established technique that can provide ideal surgical conditions and patient comfort . However, for upper arm fistula creation, e.g.…”
mentioning
confidence: 99%